Effect of two consecutive periods of drought on the limnology of three shallow reservoirs in an urban park - Borges , Jaqueline Souza; Martins , Heytor Lemos; Millan , Rodrigo Ney; Martins, Eduardo da Silva (Seven Editora, 2023)
Urban parks are used as spaces for leisure, socialization, and environmental preservation. Many parks have reservoirs in their perimeter, whose dry period can lead to a decrease in the water level, causing changes in the physicochemical variables that can provide deterioration of water quality. The objective of this work is to compare the effects of two consecutive dry periods (2019 and 2020) on the physicochemical variables of water in three shallow urban reservoirs. The collections were carried out in the park "Leda Campos Borges," located in the city of Frutal-MG, during the years 2019 and 2020. The inlet and outlet of water from each of the reservoirs were sampled. The means of the limnological data in each year of the collection were used to perform a principal component analysis (PCA) to verify the associations of the variables in the respective reservoirs with the years sampled. The Principal Component Analysis associated the variables total phosphorus, total nitrogen, dissolved oxygen, total dissolved solids, and electrical conductivity to R3-2020 and R1-2020. R2-2019 and R2-2020 are associated with the highest temperature values. R1-2019 is associated with the highest values of pH and turbidity. The worsening of the drought between 2019 and 2020 caused a decrease in water quality in reservoirs 1 and 3. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-017